Severe Skin and Soft-Tissue Infections - Stieferman, Addison E.; Mazi, Patrick; Burnham, Jason P. (Seminars in Respiratory and Critical Care Medicine, 2022)
Skin and soft-tissue infections (SSTIs) are a common reason for hospital admission. Severe SSTIs, particularly necrotizing infections, often require intensive care. Source control (often with surgical debridement) and broad-spectrum antimicrobials are paramount for minimizing significant morbidity and mortality. Rapid diagnostic tests may help in selection and de-escalation of antimicrobials for SSTIs. Besides early source control and early effective antimicrobial therapy, other patient-level factors such as comorbidities and immune status play a role in clinical outcomes. Intravenous immunoglobulin continues to be studied for severe SSTI, though recruitment in trials continues to be an issue. Severe SSTIs are complex to manage, due in part to regional variation in predominant pathogens and antimicrobial resistance patterns, as well as variations in host immune responses. This review includes descriptions of source control, antimicrobial therapies, intravenous immunoglobulin, and hyperbaric oxygen therapy, as well as host factors in severe SSTIs.
Keywords: soft-tissue infections; necrotizing fasciitis; gas gangrene